Therapeutic potential of the immunomodulatory proteins Wuchereria bancrofti L2 and Brugia malayi abundant larval transcript 2 against streptozotocin-induced type 1 diabetes in mice. Issue 5 (26th September 2016) - Amdare, N.P.; Khatri, V.K.; Yadav, R.S.P.; Tarnekar, A.; Goswami, K.; Reddy, M.V.R.
Abstract: Epidemiological and experimental evidence has supported the concept of using helminths as alternative bio-therapeutic agents in the treatment of type 1 diabetes (T1D). In the current study, two filarial proteins, recombinant Wuchereria bancrofti L2 (r Wb L2) and Brugia malayi abundant larval transcript 2 (r Bm ALT-2) have been investigated, individually and in combination, for their therapeutic potential in streptozotocin (STZ)-induced T1D. The r Wb L2 and r Bm ALT-2 proteins, when administered individually or in combination, have resulted in lowering of the blood glucose levels and reducing the incidence of T1D in mice. In addition, these proteins have led to reduced lymphocytic infiltration and decreased islet damage and inflammation. The curative effect was found to be associated with the suppression of release of tumour necrosis factor-α (TNF-α) and interferon-γ (IFN-γ), and increased production of interleukin (IL)-4, IL-5 and IL-10 cytokines by the splenocytes of the diabetic mice. Insulin-specific IgG1 and antigen-specific IgE antibodies were found to be elevated in the sera of mice treated with r Wb L2 and r Bm ALT-2 proteins. From the findings in this study, it can be envisaged that both of these filarial immunomodulatory proteins have the potential to ameliorate T1D by altering the regulatory immune responses.